Annual report audit, ESG report assurance and audit quality: Evidence from the same accounting firm - Wenwen Li; Ting Li; Hongjun Zhu (China Journal of Accounting Research)
This study investigates the impact of an accounting firm’s providing both an annual report audit and environmental, social and governance (ESG) report assurance on its audit quality. We find that when the same accounting firm is responsible for both the annual report audit and ESG report assurance, this does not compromise the accounting firm’s independence. On the contrary, it enhances audit quality through knowledge spillover effects and increased investment in reputational capital. Additional evidence suggests that providing ESG report assurance also prompts the accounting firm to allocate more audit resources, thereby influencing audit quality. In cross-sectional results, consistent with expectations, we find that the knowledge spillover and reputational effects of ESG report assurance are more pronounced for companies with weaker internal controls, non-A + H share companies and companies receiving lower levels of analyst attention. Finally, we document that having the same accounting firm responsible for ESG report assurance and annual report audit increases audit fees and also contributes to enhanced firm value. This study comprehensively highlights the influence of ESG report assurance on audit quality, and its findings offer valuable insights into the economic consequences of ESG report assurance practices.